The Book of Doors - Brown, Gareth (New York William Morrow, 2024)
Cassie Andrews works in a bookshop living an unassuming, ordinary life. When one of her favourite customers dies right in front of her, she is left with the last book he was reading. But this is no ordinary book. It's a book that promises Cassie that "any door is every door." You just need to know how to open them. The tome, now in Cassie's possession, is not the only book with great power, but it is the one most coveted by those who collect them. There are those willing to kill to obtain those secrets. And a dark force - in the form of a shadowy, sadistic woman - is at the very top of that list. Print run 100,000.
10 57
Keywords: Women booksellers -- Fiction; Books -- Fiction; Magic -- Fiction; Time travel -- Fiction; New York (N.Y.) -- Fiction; Fantasy fiction